Revealing the challenges and efforts of routine immunization coverage in Nigeria - Tolulope Joseph Ogunniyi (Health Science Reports)
Abstract Introduction Nigeria adopted the expanded program on immunization (EPI) in 1978, which aimed at offering children under 2 years old routine immunization (RI). Early accomplishments with the program resulted in a decrease in childhood mortality. As of 2018, Nigeria accounted for about 4.3 million out of over 13 million unvaccinated children globally. Therefore, this study revealed the challenges and efforts associated with RI program in Nigeria and the way forward. Methods In this perspective article, I conducted searches and extracted relevant information from publicly available sources such as Google Scholar, Pubmed, and grey literature. I employed RI, challenges, efforts, and Nigeria as the keywords. Results The 2021 Multiple Indicator Cluster Survey/National Immunization Coverage Survey reports revealed weaknesses in the program, with a national average coverage of 36%. The primary barrier to EPI across various zones is the challenge of reaching marginalized areas that were cut off from vaccination services due to operational and sociocultural issues. Some of the obstacles, such as restricted access to medical facilities, weak cold chain systems, and COVID‐19 containment strategies had a great impact on the RI program. To scale up the RI program, the Nigerian government, through the National Primary Health Care Development Agency (NPHCDA), collaborated with the World Health Organization (WHO) and Gavi, the Vaccine Alliance, to optimize the “Big Catch‐up campaign” and increase immunization coverage nationwide. By 2028, 80% of the projected zero‐dose populace is expected to be covered, reaching these eligible children with life‐saving vaccines. Conclusion Nigeria still has a long way to go in making significant progress in the RI program. To further strengthen the immunization coverage, the country needs to maintain data on their achievements, as this will help identify gaps that need to be addressed in the immunization program.